EVALUASI PENGOLAHAN KOMPOS DARI LIMBAH PADAT TANDAN KOSONG KELAPA SAWIT DI UNIT PKS SEI ROKAN PT. PERKEBUNAN NUSANTARA V (PERSERO) ROKAN HULU, RIAU - , RISTI AULIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Palmâs empty fruit bunches are one of the oil palm industryâs waste with huge potential. Empty fruit bunches contain organicâs material and nutrition for plants. Chemical composition of empty fruit bunches consist of 15% ashes, 40% cellulose, 21% lignin and 24% hemicellulose. This condition used by PKS Sei Rokan, which is one of the factoryâs unit owned by PT. Perkebunan Nusantara V (Persero) Riau to build a compost factoryâs unit from solid waste of empty bunches. Therefore, the purpose of this research is to evaluate the process of composting from empty fruit bunchesâ solid waste of palm in PKS Sei Rokanâs unit. Compostingâs evaluation of empty fruit bunchesâ solid waste of palm in PKS Sei Rokanâs unit, PT Perkebunan Nusantara V (Persero) begins with knowing ongoing compostingâs step, and then comparing resulted compost with SNI 19-7030-2004 and analyzing value added from the process of composting from empty fruit bunchesâ solid waste. The process of composting from empty fruit bunchesâ solid waste which is conducted by PKS Sei Rokan implements low technologyâs composting system with window compostingâs technique. The ongoing composting is appropriate and produces compost that fulfilled 8 of 9 parameter that is being tested. Based on applied costâs analysis, the result shows that profit from empty fruit bunchesâ solid wasteâs utilization to become compost is 3 billion rupiahs per year.